EVALUASI PEMILIHAN PENYEDIA JASA KURIR BERDASARKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Juli Astuti; Erika Fatma (Politeknik APP Jakarta, 2017)
Logistics activity plays an important role in the business process where there is a distribution process to deliver product from the manufacturer / seller to the consumer. Nowadays there are many companies that provide logistics services with its own advantages and disadvantages. This condition, gives users more flexibility in determining which courier companies they will use. IN ordr to aid decision makers in selecting the best courier services providers, we conducted a study regarding the criteria used in determining user's choice by using Analytical Hierarchy Process (AHP). The purpose of this study was to determine the main criteria as user's consideration for selecting the best logistics service providers. Based on a survey conducted on the online sellers, it is known that the criteria of the key considerations in selecting a courier service is Reliability, the reliability of a courier company in serving the needs and desires of its customers, followed by cost and convenience